2020
DOI: 10.3390/nu12123610
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Mediterranean Diet Intervention on Targeted Plasma Metabolic Biomarkers among US Firefighters: A Pilot Cluster-Randomized Trial

Abstract: Metabolomics is improving the understanding of the mechanisms of the health effects of diet. Previous research has identified several metabolites associated with the Mediterranean Diet (MedDiet), but knowledge about longitudinal changes in metabolic biomarkers after a MedDiet intervention is scarce. A subsample of 48 firefighters from a cluster-randomized trial at Indianapolis fire stations was randomly selected for the metabolomics study at 12 months of follow up (time point 1), where Group 1 (n = 24) continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 55 publications
4
26
0
Order By: Relevance
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
See 3 more Smart Citations
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
“…These results underline that in addition to the dietary transition seen the past decades in this region, the pandemic has further triggered unhealthy dietary choices that may further increase metabolic diseases, and the authors agree with Grabia and colleagues [ 2 ] and recommend dietary counseling to increase fruits, vegetables, and other foods close to the MD pattern. Moreover, the importance of dietary counseling on the lipid profile in healthy [ 6 , 7 ] and dyslipidemic individuals [ 3 ] was evident by intervention studies included in the present SI.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The choice of the recipe composition of the instant granular drink was carried out taking into account the content of ingredients that enhance the positive effect on each other and on the body as a whole from the point of view of the prevention of vitamin deficiency in firefighters-rescuers. So, having carried out a number of studies and guided by literature data, the best composition of the drink is as follows: modified potato starch, powdered sugar, concentrated chokeberry juice, black chokeberry cake, thickened curd whey, native curd whey, citric acid [8][9].…”
Section: Resultsmentioning
confidence: 99%